Radiosensitivity and the Influence of Gamma Rays Irradiation on Local Samosir Shallots - Mariati Sinuraya; Rosmayati Rosmayati; Hasanuddin Hasanuddin; Diana Sofia Hanafiah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Bulbs  of    localSamosir  Shallot  with  the  weight  ranging  from  1,3  to1,7  g  were  irradiated  by  several doses of gamma rays in order to investigate the radiosensitivity and the effects of irradiatons on the plants. Dry bulbs 2,5 months after harvest were exposed to gamma raysradiation ranging from 0 Gy to  20  Gy  to  determine  their  responses  to  radiation  stress  and  the  effective  radiation  dose  for identification of Lethal dose 50 (LD50). Percentage of shoot growth was measured on 35th days after planting. The variation in morphological and agronomic characters were also determined.  The results indicated  that  increasing  doses  of  gamma  irradiation  had  significant  effect  on  shoot  growth. Increasing  in  gamma  rays  doses  from  0  Gy  to  11Gy  had  little  effect  on  percentage  of  shoot growth.With  the  increase  in  radiation  dosesabove  11Gy,  agreat  reduction  in  percentage  of  shoot growth  was  observed  in  irradiated  bulbs  as  compared  to  control.  The  LD50  values  of  local  Samosir Shallot  determined  from  linear  regression  analysis  (using  Curve-fit  Analysis    software)  based  on percentage  of  regenerated  shoot  growth  was  11.60  Gy.  There  were  also siqnificantdifferenciesbetweenregenerated  plants  growth  from  irradiated  bulbs  and  control (unirradiated).Treated bulbs produced shorther plant lenght and less leave number